IMPLEMENTASI KURIKULUM MERDEKA BELAJAR PADA KEGIATAN BELAJAR MENGAJAR ANAK USIA DINI (STUDI KASUS DI SEKOLAH PENGGERAK TK INSAN HASANAH CIANJUR) - Nisa Nurmaulida; Wahyudin; Qudsi Mutawakil Husaini (Jurnal Pendidikan Islam dan Manajemen Ekonomi, 2025)
This study specifically examines a learning process conducted by the Ministry of Education and Culture through the implementation of a new curriculum, namely the Merdeka Curriculum. Every educational institution faces significant challenges in carrying out innovations within this educational system. The new curriculum requires considerable time and effort. Consequently, this research is essential for enhancing our understanding of the implementation of the Merdeka Curriculum, particularly in terms of planning, executing, and assessing the curriculum in early childhood education (PAUD). The primary objective of this study is to identify several issues encountered by TK Insan Hasanah Cianjur and to explain how the Merdeka Curriculum is being implemented. This research employs a descriptive approach with a qualitative method and was conducted at TK Insan Hasanah Cianjur. The subjects of this study are teachers and the school principal. Data were collected through observations, interviews, and documentation. First, the findings indicate that understanding learning outcomes and objectives, designing a sequence of learning objectives, and developing lesson plans, teaching modules, and assessments are all integral components of Merdeka Curriculum planning. Second, the evaluation of the Merdeka Curriculum encompasses activities in the opening, core, and closing stages. Moreover, TK Insan Hasanah Cianjur faces several challenges in implementing the Merdeka Curriculum, including a shortage of human resources, an educational and teaching system that has not yet been fully established, and a lack of readiness in applying this curriculum effectively.